GAMBARAN KADAR GLUKOSA DARAH PUASA PADA IBU HAMIL TRIMESTER II DAN III DI PUSKESMAS I DENPASAR SELATAN - dhyana putri (Jurusan Analisis Kesehatan, Poltekkes Kemenkes Denpasar, 2017)
AbstractBackground Gestational diabetes mellitus (GDM) was a condition of glucose intolerance that occur during pregnancy detected by examining blood glucose levels. Objective This study aims to measure fasting blood glucose levels at the second and third trimesters pregnant women in Puskesmas I Denpasar Selatan-based on certain characteristics. Methods The type of this study is descriptive and using simple random sampling technique. Samples in this study amounted to 33 women. Blood glucose levels measured by venous blood samples with hexokinase method. Result The study results obtained 28 women (84,85%) in the not risk of GDM category and five women (15,15%) in the risk of GDM category. High blood glucose levels obtained four women (12,12%) in the category 25 years and one women (3,03%) in the category 25, on the characteristics of the gestational age obtain two women (6,06%) in the second trimester and three women (9,09%) in the third trimester, on the characteristics of DM in the family obtained one women (3,03%) with a history of DM.Conclusion The conclusion of this research obtained fasting blood glucose level in trimester II and III pregnant women at Puskesmas I Denpasar Selatan ranged between 66 - 120 mg/dL. Keywords: blood glucose, pregnant women, gestational diabetes